2019
DOI: 10.1186/s12890-019-1023-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between asthma incidence and modifiable risk factors in Korean middle-aged and older adults: NHIS-HEALS 10-year cohort

Abstract: BackgroundThis study investigated the sex-specific incidence of asthma and the effects of modifiable risk factors, particularly obesity, on asthma incidence among middle-aged and older individuals in Korea.MethodsWe used data from the National Health Insurance Service-Health Screening Cohort (NHIS-HEALS), which includes health examinees aged 40–79 years in 2002–2003. In total, 459,529 participants with baseline anthropometric measurements were followed-up for 10 years and the development of asthma was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 64 publications
4
20
1
Order By: Relevance
“…The largest percentage of individuals with asthma was noticed in the non-smoking group. This is in accordance with previous research, which suggests that a greater number of asthma attacks occur when individuals smoke (Park, Jung, & Kwon, 2019). This occurs because smoking can cause inflammation of the respiratory tract (Nusa & Widyastiti, 2016).…”
Section: Characteristics Of Respondentssupporting
confidence: 92%
See 1 more Smart Citation
“…The largest percentage of individuals with asthma was noticed in the non-smoking group. This is in accordance with previous research, which suggests that a greater number of asthma attacks occur when individuals smoke (Park, Jung, & Kwon, 2019). This occurs because smoking can cause inflammation of the respiratory tract (Nusa & Widyastiti, 2016).…”
Section: Characteristics Of Respondentssupporting
confidence: 92%
“…This is not in line with previous studies, which suggest that there is a relationship between being overweight and having asthma (de Castro Mendes et al, 2019). Other research studies have revealed a relationship between being overweight and experiencing asthma only in males (Park, Jung, & Kwon, 2019). The statistical test results revealed no relationship between obesity and asthma in Indonesia.…”
Section: Relationship Between Bmi and Asthmacontrasting
confidence: 86%
“… 5 Several other studies have confirmed these findings. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Moreover, we observed in the FEAS that the risk of adult‐onset asthma related to current or past smoking was about 2.4 times higher in women compared to never smoking men. 5 Thus, our previous results suggested that women are more susceptible to the harmful effects of smoking.…”
Section: Introductionmentioning
confidence: 50%
“…However, many previous cohort studies [ 7 10 ] included only a single measurement of Body Mass Index (BMI), which ignored the dynamic feature of body weight over time. Thus, more studies are needed to assess the long-term consequences of weight change during certain life periods.…”
Section: Introductionmentioning
confidence: 99%